(untitled) (Scientific journal of the Fergana State University, 2025)
The article discusses the theoretical and methodological foundations and practices of integrating information technologies into educational processes. This issue provides the opportunity to use time and other resources effectively in managing and monitoring the educational process. The analysis of foreign experience and the possibilities of implementing it into the activities of national educational organizations are also presented.